INCLUSIVE MANAGEMENT: FOREIGN EXPERIENCE AND PROSPECTS FOR IMPLEMENTATION IN UKRAINE (INNOVATIVE ECONOMY, 2025)
Zhukovska A.Yu., Dyakiv O.P. INCLUSIVE MANAGEMENT: FOREIGN EXPERIENCE AND PROSPECTS FOR IMPLEMENTATION IN UKRAINEPurpose. The aim of this article is to study international experience in applying inclusive approaches to the management of enterprises and organizations, analyse the preconditions for implementing inclusive management in Ukraine, and develop a step-by-step set of actions for integrating principles of DEIB into the operations of domestic enterprises and organizations.Methodology of research. A systematic approach, general and special research methods were used in the study, in particular: scientific abstraction, content analysis method, historical and systematic method, step-by-step algorithm method, deduction and induction – to formulate the scientific hypothesis of the work, laws and principles; formal logical – to make theoretical generalisations, substantiate the research methodology, formulate conclusions; monographic – to study the content of inclusive management; systemic and structural – to consider the object of inclusive management.Findings. The article establishes that the most promising method of personnel management of modern enterprises and organisations is inclusive management and its main tool – the principles of DEIB, the introduction of which contributes to fundamental changes in society, reducing the level of discrimination and increasing the level of inclusion.Originality. To facilitate the process of implementation of inclusive management and its tools in the work of domestic enterprises and organisations, a step-by-step set of steps is proposed, and to regulate it, the necessity of developing a well-thought-out, comprehensive and ethical strategy for supporting diversity, ensuring equity, creating inclusion and organising belonging is argued.Practical value. The proposed recommendations can be used by specialists to facilitate the implementation of specific methods, technologies and tools of inclusive management in the work of domestic enterprises and organisations.Key words: inclusive entrepreneurship, personnel management, inclusive management, discrimination, non-discrimination, barrier-free.
Keywords: inclusive entrepreneurship; personnel management; inclusive management; discrimination; non-discrimination; barrier-free.